Production of dicalcium phosphate from Lao Cai second grade apatite ore leached by dilute hydrochloric acid - Hiep, Trinh Xuan; Truong, Nguyen Xuan; Dung, Nguyen Van; Chinh, Vu Van (Vietnam Journal of Science and Technology, 2017)
The production of Dicalcium phosphate from Lao Cai second grade apatite was investigated by leaching with dilute hydrochloric acid. Various factors affecting the process such as particle size, leaching time, leaching temperature, phosphate rock/hydrochloric acid ratio and mixing stirring speed and temperature have been studied to estimate the favor phosphate ore dissolution in relation to impurity. These parameters were fixed at a leaching time of 16 min, stirring speed of 400 rpm, temperature of 25 oC, hydrochloric acid concentration of 5 % and acid/phosphate ore mass ratio of 25 ml/ 5 g and particle size ≤ 450 µm. The produced aqueous acidic solution was neutralized in such a way that a pure dicalcium phosphate CaHPO4, is precipitated to be used as animal fodder. The production efficiency was 96.8 %.